ANALYSIS OF VITAMIN C AND B1 LEVELS IN SENDUDUK FRUIT (Melastoma malabathricum L.) USING UV-VIS SPECTROPHOTOMETRY METHOD - Rejeki Geubrina Putri; Muhammad Nasir; Abdul Gani (FKIP USK, 2020)
The fruit of